English in the Nordic Countries Connections, Tensions, and Everyday Realities - Peterson, Elizabeth; Beers Fägersten, Kristy (Taylor & Francis, 2024)
People in the Nordic states - Norway, Sweden, Finland, Denmark, and Iceland - rank as among the most proficient speakers of English in the world. In this unique volume, international experts explore how this came to be, what English usage and integration looks like in different spheres of society and the economy in these countries, and the implications of this linguistic phenomenon for language attitudes and identity, for the region at large, and for English in Europe and around the world. Led by Elizabeth Peterson and Kristy Beers Fägersten, contributors provide a historical overview to the subject, synthesize the latest research, illustrate the roles of English with original case studies from diverse communities and everyday settings, and offer transnational insights critically and in conversation with the situation in other Nordic states. This comprehensive text is the first book of its kind and will be of interest to advanced students and researchers of World/Global Englishe and English as a lingua franca, language contact and dialect studies/language varieties, language policy, multilingualism, sociolinguistics, and Nordic/Scandinavia and European studies.